A novel naphthalimide-based supramolecular gel for sensing of Fe3+ in aqueous medium and its application. (October 2022) - Jiang, Pengwei; Wu, Shang; Hu, Qiang; Yan, Xiangtao; Liu, Jutao; Fu, Shuaishuai; Wu, Lan; Zhao, Xiangfei; Yang, Quanlu
Abstract: In view of our research interests in stimuli-responsive supramolecular functional materials and ion recognition, a novel organogelator based on naphthalimide (NA) was successfully synthesized via a 3-step pathway. The obtained gelator NA could serve as a supramolecular π-gel(ONA) in 1, 2-Propanediol by a series of self-assembly driving forces, which showed bright blue aggregation-induced emission (AIE). Interestingly, the organogel ONA showed a fluorescence "turn-off" for Fe 3+ in the gel-gel state. Furthermore, the Fe 3+ coordinated organogel Fe-ONA could detect H2 PO4 − successively in fluorescence spectrum. The fluorescence responding circles ''on–off–on'' could be performed 4 times when alternating the addition of Fe 3+ and H2 PO4 − to ONA. The bonding mechanisms between supramolecular organogel (ONA) and ions were detected by a series of characterization. Even more significantly, the supramolecular gel ONA can be used to adsorb Fe 3+ from aqueous media and the adsorption percentage of ONA xerogel for Fe 3+ ions can reach up to 92.26%. Graphical abstract: Image 1 Highlights: The gelator molecular NA could self-assemble to form a π-gel with aggregation induced emission(AIE) in 1, 2-Propanediol. The fluorescence responding circle could be repeated 4 times by the sequential addition of Fe 3+ and H2 PO4 − . The supramolecular gel ONA can be used to adsorb Fe 3+ from aqueous media and detect Fe 3+ in practical samples.